The Gut-Brain axis: Influence of gut microbiota on Mental Health - Mrs. Kiruthigadharan (Tamil Psychiatry Journal, 2025)
When we think about what is inside the abdomen, the answer we get is that we start by talking about the small intestine, the large intestine, and the stomach. But scientists call the stomach- the second brain. This article describes the relationship between gut health and gut-related problems such as IBD, IBS, and ulcers and the underlying psychology. We must first understand why psychotherapy, a mental health treatment, is necessary for gut-related problems. Just as we consult a gut specialist for physical problems, visiting psychologists is also increasing in the current environment. Therefore, the main purpose of this article is to understand the connection between the mind and the gut.